2020
DOI: 10.1177/1352458519901272
|View full text |Cite
|
Sign up to set email alerts
|

Serum neurofilament light chain reflects inflammation-driven neurodegeneration and predicts delayed brain volume loss in early stage of multiple sclerosis

Abstract: Background: Serum neurofilament light chain (sNfL) is a marker of neuroaxonal injury. There is a lack of studies investigating the dynamics of relationships between sNfL levels and radiological disease activity over long-term follow-up in multiple sclerosis (MS). Objectives: To investigate the relationship among repeated measures of sNfL, lesion burden accumulation, brain volume loss and clinical measures. Methods: We investigated 172 patients in the early stages of MS (McDonald 2017 criteria). Clinical exams … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 34 publications
(73 reference statements)
0
39
1
Order By: Relevance
“…Similar findings have been reported in a few studies. 2,21 This may be also reflected by the two AUC values: NEDA-3-AUC (0.902) was higher than NEDA-BVL-AUC (0.757). This probably reflects the smaller number of patients with NEDA-BVL status compared with the NEDA-3.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Similar findings have been reported in a few studies. 2,21 This may be also reflected by the two AUC values: NEDA-3-AUC (0.902) was higher than NEDA-BVL-AUC (0.757). This probably reflects the smaller number of patients with NEDA-BVL status compared with the NEDA-3.…”
Section: Discussionmentioning
confidence: 93%
“…4,25 Studies have shown that BVL in MS correlates with brain inflammatory activity and predicts long-term disability status. 21 Slowing brain atrophy is currently one of the important markers of effective MS therapy. The study of Sormani et al 9 pointed out the relationship between NfL and NEDA-3 as well as the NEDA-BVL concept.…”
Section: Discussionmentioning
confidence: 99%
“…SET was an investigator-initiated, prospective observational cohort study involving eight centers in the Czech Republic. 13,23 Enrolment started in October/2005 and was completed in July 2009.…”
Section: Methodsmentioning
confidence: 99%
“…MI reflects astrocytic density, while NfL reflects neuro-axonal injury from any mechanism. 5759 This association perhaps reflects astrocytic involvement in neuroinflammation or in compensating for neurodegeneration. 6063 However, this finding was not replicated in the follow-up cohort and will require further study to better elucidate the relationship between the two measures.…”
Section: Discussionmentioning
confidence: 99%